Antibacterial Sensitivity of Bifidobacterium (Lactobacillus bifidus) - Miller, Lawrence G. (1967)
The antibacterial sensitivity patterns of gram-positive, nonsporeforming, anaerobic bacilli variously classed as Lactobacillus bifidus, Actinomyces bifidus, or Bifidobacterium were studied by the plate dilution method. A total of 34 strains, mostly from human feces, was studied. Three species, B. longum, B. adolescentis, and B. bifidum, were represented with 11, 11, and 6 strains, respectively. The other six strains fell into four other species. Most strains of all types resisted 100 μg/ml or more of neomycin, polymyxin B, and nalidixic acid. They were somewhat less resistant to kanamycin and still less so to streptomycin. All strains were inhibited by less than 1 μg/ml of penicillin G and erythromycin, by 3.1 units or less per ml of bacitracin, by 3.1 μg/ml or less of chloramphenicol, and by 6.2 μg/ml or less of tetracycline and lincomycin. Most strains were inhibited by 3.1 μg/ml of vancomycin. Results were very variable with cephalothin and nitrofurantoin, with some strains quite resistant. With half of the drugs tested, there were moderate differences in sensitivity between different species. These data are discussed in relation to the effect of antimicrobial agents on bifid bacilli in the normal human fecal flora, in relation to the implications thereof, and in relation to the usefulness of several agents (particularly neomycin, nalidixic acid, and polymyxin B) in selective media for Bifidobacterium.